PENGARUH PELATIHAN PLAIOMETRIK ALTERNATE LEG BOUND TERHADAP DAYA LEDAK OTOT TUNGKAI DAN KECEPATAN - Juni Artada, Ketut (Universitas Pendidikan Ganesha, 2013)
This study was aimed to find out the effect of plyometrics alternate leg bound training toward the explosive power and speed of leg mucule. The population were the male student, in class VII at SMPN 3 Sawan. The sample was taken by using simple random sampling. Furthermore, the sample was divided into two groups using ordinal pairing, there were experimental group and control group. The design of this study was the pre-test post-test control group design. The data was collected by 50 metres run test and standing broad jump and analyzed using independent t test. Based on the result of data analysis 1) Plyometrics alternate leg bound training was affecting the improvement of explosive power obtained the score of tmeasured 3,172 with significance 0,003. 2) Plyometrics alternate leg bound training was affecting the speed obtained the score of tmeasured 3,214 with significance 0,003. Could be concluded that alternate leg bound training was affecting the improvement of the explosive power and speed of leg muscle in tranning. From this study it is recommended that this research can be used as reference in conducting the next training and study.